2007
DOI: 10.1016/s0973-0508(07)80010-4
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral motor deficit in extradural hematoma: Analysis of 35 patients

Abstract: We work at one of the busiest trauma centers of the country and deal with more than 200 cases of extradural hematomas per year. The striking frequency of the association of motor deficits with extradural hematomas prompted us to take up this study and delineate the factors that could lessen the morbidity by decreasing the convalescence of the affected patients. We primarily found that the association between EDH and motor deficits was common, and early intervention resulted in faster recovery of motor power, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In one case series in Hong Kong Cheung et al [6] observed male predominance (78.7%). Similar observations regarding the male predominant were also observed by Aurangzeb et al [5], Cheung et al [6], Emejulu et al [7], Husain et al [14], Khaled et al [13] and Soon et al [9]. Among the 98 patients it was observed that in majority cases the mode of injury was motor vehicle accident 44 (44.88%) followed by assault 29 (29.58%) and fall from height 20 (20.40%).…”
Section: Discussionsupporting
confidence: 80%
“…In one case series in Hong Kong Cheung et al [6] observed male predominance (78.7%). Similar observations regarding the male predominant were also observed by Aurangzeb et al [5], Cheung et al [6], Emejulu et al [7], Husain et al [14], Khaled et al [13] and Soon et al [9]. Among the 98 patients it was observed that in majority cases the mode of injury was motor vehicle accident 44 (44.88%) followed by assault 29 (29.58%) and fall from height 20 (20.40%).…”
Section: Discussionsupporting
confidence: 80%
“…EDH is mostly located in the temporoparietal region, in approximately 70-80% of the patients, and extension to adjacent frontal and occipital areas is common (10). EDH occurs in 1-2% of head injured patients (3).…”
Section: █ Discussionmentioning
confidence: 99%
“…22 In around 70 -80 percent of children, EDH is primarily seen in the temporoparietal region, but it can also extend into the neighboring frontal area, as demonstrated in our study. 23 Arterial damage is the most common cause of bleeding in EDH, is frequently caused by a skull fracture, which is a typical finding in EDH. In other studies, the findings were comparable, with skull fracture rates ranging from 48 to 90 percent.…”
Section: Discussionmentioning
confidence: 99%